Effect of a thermokarst lake on soil physical properties and infiltration processes in the permafrost region of the Qinghai-Tibet Plateau, China - Wang, YiBo; Gao, ZeYong; Wen, Jing; Liu, GuoHua; Geng, Di; Li, XiaoBing (Science China. Earth sciences, 2014)
Changes in the hydrological processes in alpine soil constitute one of the several key problems encountered with studying wa- tershed hydrology and ecosystem stability against the background of global warming. A typically developing thermokarst lake was chosen as a subject for a study using model simulation based on observations of soil physical properties, infiltration pro- cesses, and soil moisture. The results showed that the selected thermokarst lake imposed certain changes on the soil infiltration processes and, with the degree of impact intensifying, the initial infiltration rate decreased. The greatest reduction was achieved in the area of moderate impact. However, the stable infiltration rate and cumulative infiltration gradually increased in the surface layer at a depth of 10 and 20 cm, both decreasing initially and then increasing, which is correlated significantly with soil textures. Moreover, the cumulative infiltration changed in line with steady infiltration rate. Based on a comparative analysis, the Horton model helps better understand the effect on the soil infiltration processes of the cold alpine meadow close to the chosen thermokarst lake. In conclusion, the formation of the thermokarst lake reduced the water holding capacity of the alpine meadow soil and caused the hydraulic conductivity to increase, resulting in the reduction of runoff capacity in the area of the thermokarst lake.